Perspectives on Administration in Psychiatric Hospitals - Caudill, William (Administrative Science Quarterly, 1956)
The author views the psychiatric hospital as a small society, and sees administrative procedures as part of the structure of this society. Some of the special aspects of the over-all social structure of psychiatric hospitals are described, and an attempt is made to show how these structural aspects influence the nature of the interrelations between the administrative and therapeutic processes in the hospital. In this sense, the hospital is seen by the anthropologist as a particularly advantageous context within which to study the wider problem of physiological, psychological, and social variables in illness and its treatment. Illustrative examples are drawn from current literature in the area of social science and medicine and from the author's own work in psychiatric hospitals in the United' States and' Japan. The author is on the faculty of the Department of Social Relations at Harvard' University.